2021
DOI: 10.2147/cia.s290071
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data for Gait Speed and Height Norm Speed in ≥ 60-Year-Old Men and Women

Abstract: Purpose To determine normative data for gait speed and height-normalized gait speed in community-dwelling older men and women. Materials and Methods In this cross-sectional study, we recruited 565 men and women aged ≥60 years old. Age was calculated from the date of birth and further classified into four categories: (1) 60–65 years, (2) 66–70 years, (3) 71–75 years and (4) ≥76 years. Gait speed was assessed by a pressure platform (ZEBRIS, Munich, Germany) in meters per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 19 publications
(47 reference statements)
1
15
2
Order By: Relevance
“…In this study, walking speed and height-normalized speed decreased with age and was higher in males than in females, which is in accordance with previous research [ 11 , 23 , 24 , 25 , 26 ]. Declined lower limb muscle function and fewer muscle fibers in female compared with male along with aging process and the attribution of the larger step and stride length in male may be the cause of this condition [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, walking speed and height-normalized speed decreased with age and was higher in males than in females, which is in accordance with previous research [ 11 , 23 , 24 , 25 , 26 ]. Declined lower limb muscle function and fewer muscle fibers in female compared with male along with aging process and the attribution of the larger step and stride length in male may be the cause of this condition [ 27 , 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…It has been indicated that older adults experience instability, impaired balance and reduced whole-body coordination when compared to younger adults. In addition to age, previous research has indicated that sex has an impact on both postural stability, balance and gait speed; that is, males walk faster than women, which is generally ascribed to the longer step and stride length produced by men [5,6]. However, there have been no reports of the differences between the sexes in turning tasks.…”
Section: Introductionmentioning
confidence: 99%
“…However, Kasović et al [ 36 ] reported a dependence regarding a higher body mass index in women, significantly associated with slower gait speed. Apparently, our results were not confounding by anthropometric measures, because both groups were homogenous in regard to BMI.…”
Section: Discussionmentioning
confidence: 99%